Opportunities and challenges in teacher recruitment and retention : teachers' voices across the pipeline - Rinke, Carol R.; Mawhinney, Lynnette, 1979- (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Opportunities and Challenges in Teacher Recruitment and Retention serves as a comprehensive resource for understanding teachers' careers across the professional lifespan. Grounded in the notion that teachers' voices are essential for understanding teachers' lives, this edited volume contains chapters that privilege the voices of teachers above all. Book sections look closely at the particular issues that arise when recruiting an effective, committed, and diverse workforce, as well as the challenges that arise once teachers are immersed in the classroom setting. Promising directions are also included for particularly high-need areas such as early childhood teachers, Black male teachers, STEM teachers, and urban teachers. The book concludes with a call for self-care in teachers' lives"-- Provided by publisher.
Keywords: Teachers -- Recruiting -- United States.; Teacher turnover -- United States.; Teachers -- United States -- Social conditions.; School personnel management -- United States.; Career development -- United States.; Education -- Administration -- General.; Teaching staff.; Educational administration and organization.; elektronické knihy; electronic books